Etiology unknown: Qualitative analysis of patient attributions of causality in scleroderma. Issue 2 (June 2018) - Gholizadeh, Shadi; Drizin, Julia H; Hansdottir, Ingunn; Weisman, Michael H; Clements, Philip J; Furst, Daniel E; Malcarne, Vanessa L
Background: Questions about the etiology of disease can concern patients living with any chronic disease and may impact disease-related adjustment. These causal attributions may be of particular interest when individuals are living with diseases for which etiologies have not been definitively identified, such as scleroderma. This study qualitatively explored patient attributions of causality for scleroderma. Methods: Patients with confirmed diagnoses of scleroderma responded to an open-ended prompt. The cross-sectional sample of scleroderma patients ( N = 114) was recruited through registries maintained at the University of California, Los Angeles and University of California, San Diego Schools of Medicine and the Virginia Mason Medical Center. Content analysis was used to analyze the qualitative data and group the responses via an inductively derived codebook using the text analysis tool Dedoose Version 4.5. Results: Patients provided a variety of possible causes for scleroderma, which grouped into seven themes: (1) stress, (2) environment, (3) genetics, (4) medical conditions or surgeries, (5) diet, (6) medications or substance use, and (7) spirituality. Conclusion: Patients' causal attributions for scleroderma were varied, but many patients identified stress as a cause of scleroderma, often focusing on acute or chronic stressors that were present before disease onset. Identifying patient theories of causality for scleroderma can contribute to an increased understanding of disease-related behaviors and adjustment.